Internationalization of the curriculum for the training of global skills (Revista Electrónica REDINE, 2021)
The internationalization of the curriculum has been considered an institutional strategy, the actions are oriented towards the training of professionals who compete with the competencies required to perform adequately in world environments. Its meaning has expanded as new actions are incorporated in practice in response to the changing contexts associated with globalization. In this sense, the present work aims to analyze various conceptions and perspectives on the internationalization of the curriculum, from the contextualization of internationalization in higher education and then derive some criteria that contribute to the training of professionals with global competencies. Aspects of the globalization and internationalization of higher education and the internationalization of the curriculum were developed, as theoretical support that finally allowed generating, from a comprehensive vision, general and micro-curricular criteria with the end of internationalize the university curriculum at Yacambú University.
Keywords: internationalization of the curriculum; training; global skills